Potential Bases of Physical Modification of Local Minerals-Heterocomposite Polymer Materials (Texas Journal of Engineering and Technology, 2023)
The article explains that "Angren Kaolin" LLC produces enriched kaolin of AKF-78, AKS-30, AKT-10 brands, Kaolin AKF-78, mainly used as a filler in paper production and its unique properties include excellent adhesion and a high kaolin particle thickness ratio of 30:1 and solar curing of the polymer composition to control the strength response in the preparation of highly viscous epoxy composites using GS in a 10:10 (w/w) ratio with DBF, high-viscosity epoxy compositions using gossypol resin in a ratio of 50:50 with DBP, which is an effective way to save energy, and solar treatment of the polymer composition is important in their practical application in the industry for technological equipment and products operating under conditions of corrosion-hydroabrasive corrosion save energy in cooking, effective way to control the hardening reaction